The Malaysian Property Boom and Bust Cycle: History Repeating? - Carmelo Ferlito (World Economics Association, 2018)
According to Mark Thornton, we could be very close to another major economic crisis. Ten years have passed from the so-called Great Recession and Thornton's prediction confirms my view according to which business fluctuations are pervasive, and the crisis that emerged in the Western world in 2007 is just the latest and most evident manifestation of such dynamics. I have expressed the idea that business cycles are unavoidable by developing the doctrine of the natural cycle. In the present paper I used that framework in order to describe the evolution of the Malaysian property market in the last decade in the context of the general development of the national economy. In fact, it seems that this evolution presents many features of the cyclical dynamic that brought about the Great Recession after a ten year delay.
Conference: World Economics Association (WEA) Conferences, No. 2 2018, The 2008 Economic Crisis Ten Years On, 15th October to 30th November, 2018
Keywords: E32; O16; 330; business cycles; Malaysia; property market; expectations